LARANGAN PENGASINGAN TANAH DAN PELUANG INVESTASI ASING DI INDONESIA - Sumarja, FX (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2014)
Throughout the political history, agrarian law in Indonesia recognize the prohibition of land alienation. Foreigners orÂ foreignÂ legalÂ entitiesÂ (foreignÂ investors) wereÂ bannedÂ forÂ landÂ ownership.Â ArgrarianÂ FundamentalÂ Lawsstipulates that foreigners domicile in Indonesia and foreign legal entities which have representatives in Indonesia areÂ onlyÂ allowedÂ to haveÂ landÂ useÂ rightsÂ andÂ buildingÂ leaseÂ rights.Â InÂ practice,Â foreignersÂ andÂ foreignÂ legalentities preferÂ toÂ acquireÂ landÂ ownershipÂ rights by nominee. WhereasÂ nomineeÂ isÂ illegalÂ andÂ hasÂ very weak legal position. Article 16 paragraph (1) letter h junto Article 24 Argrarian Fundamental Laws open the opportunitiesfor foreign investorsÂ in land tenure through Guna Bangun Serah rights, by positioning the ground as a means of productionÂ ratherÂ than as anÂ investment. Guna Bangun SerahÂ inÂ Indonesia was marked by the birth ofÂ theMinister of Finance ofÂ the Republic of Indonesia Decree No. 470 / KMK.01Â / 1994 on Procedures for Removal and Utilization of AssetsÂ / Countryâs Wealth, which adoptedÂ theÂ âTurgutâs Formulaâ, namelyÂ the construction and management of dams on the river Syehan Turkey.This study aims to find an alternative land ownership for foreignÂ investors thatÂ requireÂ land asÂ ingredients, consideringÂ theÂ limitedÂ tenureÂ inÂ IndonesiaÂ to considerÂ theexpediencyÂ ofÂ justiceÂ andÂ legalÂ certainty.Â TheÂ newÂ paradigmÂ is neededÂ inÂ attractingÂ foreignÂ investmentÂ in Indonesia, in order to obtain the benefit, justice and legal certainty, through Bangun Guna Serah rights. Article 16 paragraph (1) letter h Argrarian Fundamental Laws stipulates the other rights that are not included: Properties, CultivationÂ rights, BuildingÂ rights,Â TenureÂ and RentalÂ Rights willÂ beÂ establishedÂ byÂ law.Â Bangun GunaÂ Serah rights defined as rights to construct a building and / or its facilities on land that is not his own and then utilize the building andÂ / orÂ its facilitiesÂ in aÂ certain period ofÂ time that has been agreed, asÂ inÂ theÂ future theÂ land, buildingsÂ andÂ / orÂ theÂ followingÂ facilities will beÂ transferedÂ toÂ the owner ofÂ theÂ land afterÂ theÂ term expired. Guna Bangun SerahÂ rightsÂ can beÂ incorporated intoÂ the Land Bill.